Letter from Eugène Lemercier to his mother, Marguerite Lemercier, expressing his hope that this violence will lead to a better tomorrow - Lemercier, Eugène Emmanuel, 1886-1915; Lemercier, Marguerite, 1859-ca. 1930 (1914)
Shares his thoughts about the transitory and earthly nature of war and choses to focus his mind on what is eternal, on a "ordre supérieur" and a "destinée universelle". Mentions the Cadoux.
Addressed to "Madame Lemercier / 40 Rue Lauriston / Paris". No postmark.
The letter folds itself into an envelope.
Postscript on envelope informing recipient that he has written to their "pauvre amie" Marthe [perhaps Mrs Rapp or Mrs Cadoux].
Pencil is fading.
Lettres d'un soldat (août 1914-avril 1915) : Préface de André Chevrillon / [Eugène Lemercier]. Paris : Librairie Chapelot, 1916.
Lettres d'un soldat (août 1914-avril 1915) : Présentées par Bernard Giovanangeli / Eugène Emmanuel Lemercier. Paris : Bernard Giovanangeli Editeur, 2013.
Keywords: Lemercier, Eugène Emmanuel, -- 1886-1915 -- Correspondence; World War, 1914-1918 -- France; World War, 1914-1918 -- France -- Correspondence; France -- History -- 1914-1940